Modern types of excursion activities - Dolynska, Olesia; Hutsal, Liudmyla; Dolynskiy, Ievgen (Journal of Education, Health and Sport, 2024)
Today, tourism is gaining increasing popularity worldwide and represents a sector with positive growth dynamics. Excursion activities are an important component of tourism. Modern excursion activities are rapidly evolving to meet the growing demands of tourists for new experiences and interactive formats. Excursions today are no longer limited to traditional forms of exploring cultural or historical landmarks; instead, they take on a creative and even adventurous character. Key modern trends in excursion activities include quest excursions, historical reenactment tours, thematic, and interactive tours, which allow participants to deeply immerse themselves in the ambiance of a place, feeling like a part of history or culture. Quest excursions combine the traditional format with interactive tasks, enabling tourists not only to observe but also actively participate in exploration. This makes excursions more emotionally engaging and suitable for various age groups. Historical reenactment tours, where participants can immerse themselves in past eras through the reconstruction of daily life, attire, and traditions, are also gaining popularity. The article presents current trends in excursion activities. These activities create a unique atmosphere that allows for a deeper appreciation of the culture or genre. They may include mythological or legendary journeys where tourists uncover ancient mysteries, or nighttime excursions with a mystical ambiance. Interactive tours also push the boundaries of the traditional format by including elements of virtual reality, QR codes for self-guided information access, and workshops that let participants acquire new skills. Digital technologies are becoming a significant part of the excursion process: Virtual reality and augmented reality (AR) means provide the opportunity to virtually travel anywhere in the world without leaving one’s hometown. This format becomes particularly relevant during pandemics or for people with limited mobility. Interactive and thematic excursions meet modern tourists' expectations, transforming excursions into exciting adventures and significantly expanding the potential of excursion activities.